The dynamic and spatial distribution analysis of labour condition in Lampung Province before and during the COVID-19 - Alfi, F. (EDP Sciences, 2023)
This study aims to determine the Labour Force Participation Rate (LFPR), Employment to Population Ratio (EPR), Open Unemployment Rate (OUR), Underemployment Rate (UER), labour force and open unemployment based on education, gender, and rural-urban areas. It examines the employment conditions of Lampung Province before COVID-19 based on the years 2017-2019, while during COVID-19 based on the year 2020. The analysis carried out is a quantitative and qualitative descriptive method using secondary data from SAKERNAS 2017-2020. The results show that Lampung Province's LFPR level has an insignificant upward trend from 2017-2020 with an average increase of 0.77. The EPR tends to increase from year to year except in 2019 which decreased by 0.56. OUR decreased by 0.29 in 2018, was constant in 2019, and increased dramatically in 2020 by 0.64. The workforce according to the highest education has increased in 2017-2020. The number of workforce 2017-2020 in rural areas is twice as much as in urban areas, with the characteristics of the growth of the workforce always being accompanied by an increase in the number of unemployed. The population of the Lampung Province workforce in 2017-2020 is still male dominated, a gap in job opportunities for the female population still exists. © 2023 EDP Sciences. All rights reserved.